Application of the Meerwein reaction of 1,4-benzoquinone to a metal-free synthesis of benzofuropyridine analogues - Singh, Rashmi; Horsten, Tomas; Prakash, Rashmi; Dey, Swapan; Dehaen, Wim (Beilstein Journal of Organic Chemistry, 2021)
Several new heterocyclic systems based on a hydroxybenzofuro[2,3-b]pyridine building block were prepared. This benzofuropyridine is easily available from the Meerwein reaction of benzoquinone and a heterocyclic diazonium salt, followed by reduction and cyclization. Electrophilic substitution and further condensations give polycyclic systems, including oxazolo- and chromeno-fused analogues.
Keywords: benzofuropyridines; benzoquinones; dibenzofurans; Meerwein reaction; metal-free synthesis

(untitled) - Shou, Q.; Banbury, L. K.; Renshaw, D. E.; Lambley, E. H.; Mon, H.; Macfarlane, G. A.; Griesser, H. J.; Heinrich, M. M.; Wohlmuth, H. (J. Nat. Prod., 2012)

(untitled) - Setzer, W. N.; Rozmus, G. F.; Setzer, M. C.; Schmidt, J. M.; Vogler, B.; Reeb, S.; Jackes, B. R.; Irvine, A. K. (J. Mol. Model., 2006)

(untitled) - De Lombaert, S.; Blanchard, L.; Stamford, L. B.; Tan, J.; Wallace, E. M.; Satoh, Y.; Fitt, J.; Hoyer, D.; Simonsbergen, D.; Moliterni, J.; Marcopoulos, N.; Savage, P.; et al. (J. Med. Chem., 2000)

(untitled) - Kaul, R.; Deechongkit, S.; Kelly, J. W. (J. Am. Chem. Soc., 2002)

(untitled) - Carney, J. R.; Krenisky, J. M.; Williamson, R. T.; Luo, J. (J. Nat. Prod., 2002)

(untitled) - Petrassi, H. M.; Johnson, S. M.; Purkey, H. E.; Chiang, K. P.; Walkup, T.; Jiang, X.; Powers, E. T.; Kelly, J. W. (J. Am. Chem. Soc., 2005)

(untitled) - Momotake, A.; Lindegger, N.; Niggli, E.; Barsotti, R. J.; Ellis-Davies, G. C. R. (Nat. Methods, 2006)

(untitled) - Fang, L.; Fang, X.; Gou, S.; Lupp, A.; Lenhardt, I.; Sun, Y.; Huang, Z.; Chen, Y.; Zhang, Y.; Fleck, C. (Eur. J. Med. Chem., 2014)

(untitled) - Lin, R.-D.; Chen, M.-C.; Liu, Y.-L.; Lin, Y.-T.; Lu, M.-K.; Hsu, F.-L.; Lee, M.-H. (Int. J. Mol. Sci., 2015)

(untitled) - Love, B. E. (Eur. J. Med. Chem., 2015)

(untitled) - Ito, T.; Sasabe, H.; Nagai, Y.; Watanabe, Y.; Onuma, N.; Kido, J. (Chem. – Eur. J., 2019)

(untitled) - Francisco, C. S.; Rodrigues, L. R.; Cerqueira, N. M. F. S. A.; Oliveira-Campos, A. M. F.; Rodrigues, L. M. (Eur. J. Med. Chem., 2012)

(untitled) - Oliveira, A. M. A. G.; Raposo, M. M. M.; Oliveira-Campos, A. M. F.; Griffiths, J.; Machado, A. E. H. (Helv. Chim. Acta, 2003)

(untitled) - Duan, W.; Rangan, A.; Vankayalapati, H.; Kim, M. Y.; Zeng, Q.; Sun, D.; Han, H.; Fedoroff, O. Y.; Nishioka, D.; Rha, S. Y.; Izbicka, E.; Von Hoff, D. D.; et al. (Mol. Cancer Ther., 2001)

(untitled) - Wichapong, K.; Lindner, M.; Pianwanit, S.; Kokpol, S.; Sippl, W. (Eur. J. Med. Chem., 2009)

(untitled) - Eduardo Paiva Sena Maia, J.; de Lucas, N. C.; Cesarin-Sobrinho, D.; da Hora Machado, A. E.; Netto-Ferreira, J. C. (J. Photochem. Photobiol., A, 2016)

(untitled) - Yempala, T.; Sridevi, J. P.; Yogeeswari, P.; Sriram, D.; Kantevari, S. (Bioorg. Med. Chem. Lett., 2013)

(untitled) - Prado, S.; Ledeit, H.; Michel, S.; Koch, M.; Darbord, J. C.; Cole, S. T.; Tillequin, F.; Brodin, P. (Bioorg. Med. Chem., 2006)

(untitled) - Balasubramanian, G.; Narayanan, S.; Andiappan, L.; Sappanimuthu, T.; Thirunavukkarasu, S.; Sundaram, S.; Natarajan, S.; Sivaraman, N.; Rajagopal, S.; Nazumudeen, F. A. A.; Saxena, S.; Vishwakarma, S. L.; et al. (Bioorg. Med. Chem., 2016)

(untitled) - Brachwitz, K.; Hilgeroth, A. (Bioorg. Med. Chem. Lett., 2002)

(untitled) - Krug, M.; Voigt, B.; Baumert, C.; Lüpken, R.; Molnár, J.; Hilgeroth, A. (Eur. J. Med. Chem., 2010)

(untitled) - Krug, M.; Erlenkamp, G.; Sippl, W.; Schächtele, C.; Totzke, F.; Hilgeroth, A. (Bioorg. Med. Chem. Lett., 2010)

(untitled) - Voigt, B.; Krug, M.; Schächtele, C.; Totzke, F.; Hilgeroth, A. (ChemMedChem, 2008)

(untitled) - Tell, V.; Mahmoud, K. A.; Wichapong, K.; Schächtele, C.; Totzke, F.; Sippl, W.; Hilgeroth, A. (Med. Chem. Commun., 2012)

(untitled) - Brachwitz, K.; Voigt, B.; Meijer, L.; Lozach, O.; Schächtele, C.; Molnár, J.; Hilgeroth, A. (J. Med. Chem., 2003)

(untitled) - Voigt, B.; Meijer, L.; Lozach, O.; Schächtele, C.; Totzke, F.; Hilgeroth, A. (Bioorg. Med. Chem. Lett., 2005)

(untitled) - Tell, V.; Holzer, M.; Herrmann, L.; Mahmoud, K. A.; Schächtele, C.; Totzke, F.; Hilgeroth, A. (Bioorg. Med. Chem. Lett., 2012)

(untitled) - Prado, S.; Toum, V.; Saint-Joanis, B.; Michel, S.; Koch, M.; Cole, S.; Tillequin, F.; Janin, Y. (Synthesis, 2007)

(untitled) - Meerwein, H.; Büchner, E.; van Emster, K. (J. Prakt. Chem., 1939)

(untitled) - Fujiwara, Y.; Domingo, V.; Seiple, I. B.; Gianatassio, R.; Del Bel, M.; Baran, P. S. (J. Am. Chem. Soc., 2011)

(untitled) - Itahara, T. (J. Org. Chem., 1985)

(untitled) - Waldvogel, S. R.; Lips, S.; Selt, M.; Riehl, B.; Kampf, C. J. (Chem. Rev., 2018)

(untitled) - T.P, A. K.; Pandaram, S.; Ilangovan, A. (Org. Chem. Front., 2019)

(untitled) - Wang, L.; Shen, J.; Yang, S.; Liu, W.; Chen, Q.; He, M. (Green Chem., 2018)

(untitled) - Fürst, M. C. D.; Gans, E.; Böck, M. J.; Heinrich, M. R. (Chem. – Eur. J., 2017)

(untitled) - Schroll, P.; Hari, D. P.; König, B. (ChemistryOpen, 2012)

(untitled) - Wang, Y.; Zhu, S.; Zou, L.-H. (Eur. J. Org. Chem., 2019)

(untitled) - Miliutina, M.; Janke, J.; Hassan, S.; Zaib, S.; Iqbal, J.; Lecka, J.; Sévigny, J.; Villinger, A.; Friedrich, A.; Lochbrunner, S.; Langer, P. (Org. Biomol. Chem., 2018)

(untitled) - Carlson, B. W.; Miller, L. L. (J. Am. Chem. Soc., 1985)

(untitled) - Vroemans, R.; Verhaegen, Y.; Dieu, M. T. T.; Dehaen, W. (Beilstein J. Org. Chem., 2018)

(untitled) - Gia, O.; Uriarte, E.; Zagotto, G.; Baccichetti, F.; Antonello, C.; Marciani-Magno, S. (J. Photochem. Photobiol., B, 1992)